Effects of a novel consensus bacterial 6-phytase variant on the apparent ileal digestibility of amino acids, total tract phosphorus retention, and tibia ash in young broilers. (6th February 2022) - Dersjant-Li, Yueming; Abdollahi, M Reza; Bello, Abiodun; Waller, Katie; Marchal, Leon; Ravindran, V
Abstract: The effect of a novel consensus bacterial 6-phytase variant (PhyG) on apparent ileal digestibility (AID) of amino acids (AA) and phosphorus (P) utilization in young broilers when added to diets with high phytate-P (PP) content without added inorganic phosphate (Pi) and deficient in digestible (dig) AA and metabolizable energy (ME) was investigated. A total of 256 Ross 308 male broilers were assigned to 4 treatments (8 birds/cage, 8 cages/treatment) in a completely randomized design. Treatments comprised a positive control (PC, 2, 975 kcal/kg ME, 3.7 g/kg dig P, 2.83 g/kg PP, 8.4 g/kg Ca, 10.6 g/kg dig lysine), a negative control (NC) without added Pi (ME −68 kcal/kg, crude protein −10 g/kg, dig AA −0.1 to −0.4 g/kg, Ca −2.0 g/kg, dig P −2.2 g/kg, Na −0.4 g/kg vs. PC), and NC plus 500 or 1, 000 FTU/kg of PhyG. Test diets were corn/soy/rapeseed-meal/rice-bran-based and fed from 5 to 15 d of age. Ileal digesta and tibias were collected on day 15. Excreta was collected during days 12 to 15 to determine P retention. The NC (vs. PC) reduced ( P < 0.05) P retention (−10.4% units), tibia ash (−14.3% units), weight gain (−109 g), feed intake (−82 g) and increased FCR (from 1.199 to 1.504), confirming that the NC was extremely deficient in nutrients and energy. Phytase addition to the NC linearly ( P < 0.001) improved performance, but did not fully recover it to the level of the PC due to the severe nutrients/energy reduction in NC. Phytase linearly increased P retention ( P < 0.001), tibia ash ( P < 0.001), AID of dry matter ( P < 0.05), nitrogen ( P < 0.01), gross energy ( P < 0.05), and all 17 individual AA ( P < 0.01). At 1, 000 FTU/kg, phytase increased ( P < 0.05) P retention vs. PC and NC (+14.5 and +24.9% units, respectively) and increased tibia ash vs. NC (+13.8% units), equivalent to PC. The NC decreased AID of Cys, Gly, Thr, and Met vs. PC ( P < 0.05). At 1, 000 FTU/kg, phytase increased AID of all 17 AA vs. NC ( P < 0.01), equivalent to PC. At 1, 000 FTU/kg, AID AA responses (above NC) ranged from +4.5% (Met) to +15.0% (Cys), being maximal for essential Thr (+10.4%) and Val (+8.2%) and non-essential Cys (+15.0%) and Gly (+10.4%). The results highlight the efficacy of PhyG at a dose level of 500 to 1, 000 FTU/kg in young broilers for improving the ileal digestibility of nitrogen, AA, and energy alongside P retention and tibia ash. The performance data emphasize the need to consider digestible nutrient intake as a response variable in exogenous enzyme studies. Lay Summary: Microbial phytase is widely used in commercial broiler diets to improve digestion of phosphorus (P) and reduce its excretion into the environment. Phytase improves the digestion of phosphorus and other nutrients including amino acids (AA). This study evaluated the effect of a novel consensus bacterial 6-phytase variant (PhyG) added to a nutrient-reduced diet without any added inorganic P on the digestibility of nutrients including P and AA in the ileum of young broilers. Effects on P retention and bone mineralization were also assessed. Compared to an unsupplemented negative control diet, PhyG improved growth performance, P retention, bone mineralization (tibia ash), digestibility of dry matter, nitrogen, gross energy, and all 17 individual AA during 5 to 15 d post-hatch, in a dose-dependent manner (dose range 0 to 1, 000 phytase units [FTU] per kilogram of feed). For some AA, the increases in digestibility with PhyG at 1, 000 FTU/kg were substantial (cysteine: +15.0%, threonine:+10.4%), and for all AA were equivalent to the responses produced by a nutritionally adequate positive control (unsupplemented) diet. The results demonstrate the efficacy of PhyG to improve AA digestibility alongside growth performance, P retention, and bone mineralization in young broilers. Abstract : A novel microbial 6-phytase added to a phytate-rich diet containing no added inorganic phosphate improved growth performance, amino acid and energy digestibility, phosphorus retention, and tibia ash in a dose-dependent manner in young broilers.